Kinetics of the BrO + ClO reaction and implications for stratospheric ozone - Hills, AJ; Cicerone, RJ; Calvert, JG; Birks, JW (eScholarship, University of California, 1988)
The gas-phase reaction between BrO and CIO has been proposed as a potentially fast and synergistic mechanism of stratospheric ozone destruction. Further, it has been advanced1as a contributing factor to Antarctic springtime ozone column losses of ∼40% from 1960 to 19852,3Both dynamical4and chemical theories1,5-8have been advanced to explain the formation of the Antarctic 'ozone hole'. A major uncertainty in these theories has been the rate constant and product distribution of the BrO + ClO reaction as a function of temperature. Here we report the first direct measurements of these parameters. We show that this reaction could, indeed, account for a large fraction of the springtime ozone depletion over Antarctica and provide a source of chlorine dioxide of sufficient magnitude to explain the recent measurements of this species in the Antarctic stratosphere, provided that the stratosphere contains a sufficient quantity of bromine (∼20 p.p.t.v.). © 1987 Nature Publishing Group.